Juridical Analysis of The Management of Sugarcane Plantation Rights in Boalemo Regency - Gunawan Rena; Dolot Alhasni Bakung; Fitran Amrain (Yayasan Cerdas Pedia Indonesia, 2026)
The maladministration of Sugarcane Plantation Rights (HGU) in Boalemo Regency has ignited structural conflicts, profoundly distorting agrarian justice and the social function of land. This normative legal research aims to analyze governance anomalies resulting in the deprivation of local communities' living spaces, while formulating a reconceptualization of oversight grounded in the Green Constitution and ecocracy. Utilizing statutory, conceptual, and case approaches, this study demonstrates that the formal legality of land registration instruments is frequently reduced to legitimize land commodification and ecological exploitation by corporate entities. The systemic failure of land authorities to evaluate the environmental obligations of right holders empirically creates a phenomenon of rightlessness for affected citizens. Therefore, this article concludes that a radical transformation of land governance is absolutely imperative. Oversight mechanisms must no longer rely rigidly on formal administrative procedures, but must integrate ecosystem sustainability parameters as mandatory prerequisites to effectively halt land grabbing and restore justice.